Wind power and the cost of local compensation schemes: A Swedish revenue sharing policy simulation - Erik Lundin (Research Institute of Industrial Economics (IFN), 2023)
Local resistance towards wind power is a central challenge for the energy transition, implying that legally imposed compensation schemes for nearby residents may become more prevalent in the near future. In this study, I use GIS-coded data on detached residential buildings in Sweden to simulate a variety of revenue sharing schemes applied to every present and planned commercial scale wind power project, with a focus on documenting the impact on investor costs. I compare models that entitle compensation for distance between six and ten times the tip height of the closest turbine, imposing schemes that are both constant within the eligible distance, as well as declining with distance from the turbine. An important conclusion is that costs vary considerably depending on the model chosen. When compensations are awarded for residents as far away as ten times the turbine height, foregone revenues exceed two percent for a large share of the projects, potentially necessitating the inclusion of a regulated cap on compensation costs.
Keywords: H23; D62; D4; P18; P48; 330; Wind power; negative externalities; local acceptance; energy transition; NIMBYism